Influence of timing delay on monofin intracycle swimming velocity - Rejman, M. (Biomechanics and Medicine in Swimming X, 2006)
The aim of the study was to analyze the temporal delay of the body segments and monofin movements while generating propulsion. Swimmers were filmed under water while covering 50m distance without breathing. Input data as time series of kinematics parameters of the points marked on the swimmers bodies and on the monofin were recorded on the basis of randomly filmed single cycles for each swimmer. The data showed inversely proportional relationship between the sum of vertical velocities of the reference points (SVVER) and the horizontal velocity of the swimmers' center of mass, indicating the significance of the SVVER in generating propulsion. Our study further indicated that the analysis of temporal delays of the time structure in the body segments and monofin tailored for swimmers according to the leg movements and equipment used will allow elimination of the hip and the lower thigh mistakes.